2013
DOI: 10.1093/brain/aws325
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ASIC1 in primary progressive multiple sclerosis: evidence of neuroprotection with amiloride

Abstract: Neurodegeneration is the main cause for permanent disability in multiple sclerosis. The effect of current immunomodulatory treatments on neurodegeneration is insufficient. Therefore, direct neuroprotection and myeloprotection remain an important therapeutic goal. Targeting acid-sensing ion channel 1 (encoded by the ASIC1 gene), which contributes to the excessive intracellular accumulation of injurious Na(+) and Ca(2+) and is over-expressed in acute multiple sclerosis lesions, appears to be a viable strategy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 33 publications
1
88
0
6
Order By: Relevance
“…These findings collectively support the potential efficacy of ASIC1 as a protective target for axon degeneration associated with active MS. Consistent with the pivotal role of ASIC1 in the animal model of MS, studies by Arun et al [47] showed that amiloride exerts a neuroprotective effect in patients with primary progressive MS. The normalized annual rate of whole-brain volume during the amiloride treatment phase (3 years) was significantly reduced, compared to the pretreatment phase.…”
Section: Asics and Multiple Sclerosismentioning
confidence: 67%
“…These findings collectively support the potential efficacy of ASIC1 as a protective target for axon degeneration associated with active MS. Consistent with the pivotal role of ASIC1 in the animal model of MS, studies by Arun et al [47] showed that amiloride exerts a neuroprotective effect in patients with primary progressive MS. The normalized annual rate of whole-brain volume during the amiloride treatment phase (3 years) was significantly reduced, compared to the pretreatment phase.…”
Section: Asics and Multiple Sclerosismentioning
confidence: 67%
“…It was further shown that ASIC1a is upregulated in lesions from experimental autoimmune encephalomyelitis in mice and from MS patients (Vergo et al, 2011). Treatment with amiloride was neuroprotective in animal models and in human MS patients (Vergo et al, 2011;Arun et al, 2013). Interestingly, an association between the ASIC2 gene and MS has been shown in a remote human population in Sardinia (Bernardinelli et al, 2007).…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 98%
“…As neurofibrillary tangles and amyloid plaque are also involved in pathology of Parkinson's disease and blocks transmission through cortex region or perforant tracks from areas of association of isocortex to hippocampus and cause memory impairment thus same targets as that of Alzheimer's can work for the treatment of the disease by inhibition by the above mentioned constituents of pearl millet [19]. In multiple sclerosis, MMP9 and ASIC1a elevated levels cause havoc by increasing the ion concentrations and early relapse which can be targeted and inhibited effectively by glycosylorientin, glycosylvetixin and vitexin (for MMP) and pelargonidin and quercetin (for ASIC1a), proving their efficiency to cure this disease [18]. So, our hypothesis of using nutraceutical property of pearl millet as a potential treatment for the majority of neurodegenerative disorders is having a great scope as suggested by our docking results.…”
Section: Discussionmentioning
confidence: 99%
“…Another one is multiple sclerosis in which levels of MMP9 are elevated and becomes the cause of relapsing condition in short duration [17]. ASIC1a is also known to express increasingly and are a potent target for multiple sclerosis as they are responsible for the accumulation of intracellular ions of sodium and calcium and causes injurious symptoms of the disease [18]. So, we considered MMP9, MMP2, Aquaporin 4, ASIC1a and PKC as major targets for our in silico study on NDs treatment.…”
Section: Introductionmentioning
confidence: 99%